Review of Sister Province between East Java Province-Indonesia and Prefecture Osaka-Japan - Tonny Dian Effendi (Andalas Journal of International Studies (AJIS))
The cooperation between East Java province of Indonesia and Osaka Prefecture of Japan is one of the oldest sub-national or local government’s international cooperation in both countries. The cooperation has been growing both in scope of fields and areas. From East Java perspective, the cooperation should to be more intensive on investment and workers capabilities, while Osaka views that the increasing of human resources is important point. Both of local government agree that their cooperation is important as the back-bond of Indonesia-Japan bilateral relations, and the focus on trade and economy should to be expand. Small Medium Enterprises (SMEs) is one of the priority of them now. But, they also face the challenges in the infrastructure and clear information provided. The involvement of local government under provincial/prefectural level and non-government actors including universities and NGO is needed and synergized with the cooperation.